The Influence of Organizational Culture and Motivation on Employee Performance During the Covid-19 Pandemic at PT. Perkebunan Nusantara III (Persero) Medan - Har Reza Asanah; Onan Marakali Siregar (International Journal Labs, 2022)
HR effectively and efficiently can affect the survival and growth of the organization in the midst of the Covid-19 pandemic. In order to achieve the company's goals, PT. Perkebunan Nusantara III (Persero) Medan requires qualified human resources. Quality human resources can be influenced by the motivation of the employees themselves or by the company's organizational culture. High work motivation will make employees more active at work. This motivation is also supported by the AKHLAK culture (Many, Competent, Harmonious, Loyal, Adaptive, Collaborative) owned by PT. Perkebunan Nusantara III (Persero) Medan. This will assist employees in improving their performance so that the company achieves its vision, mission, and goals. This study aims to analyze the influence of motivation and organizational culture on employee performance during the Covid-19 pandemic at PT. Perkebunan Nusantara III (Persero) Medan. The form of research used in this research is quantitative research with an associative approach. Sampling was done through the probability sampling technique and used 90 respondents as samples. The results of this study indicate that the motivation variable (X1) and the variable (X2) have an effect on employee performance. The adjusted R square value shows that the motivation and organizational culture variables contribute 38.1% to the employee performance variable. The conclusion of this study is that the motivation variable (X1) affects employee performance, organizational culture (X2) affects employee performance, and the motivational variable (X1) and organizational culture (X2) simultaneously affect employee performance.